Oral Hygiene Status, Periodontal Status, and Periodontal Treatment Needs among Institutionalized Intellectually Disabled Subjects in Kolhapur District, Maharashtra, India. (7th December 2014) - Kadam, Nilima S.; Patil, Rahul; Gurav, Abhijit N.; Patil, Yojana; Shete, Abhijeet; Naik Tari, Ritam; Agarwal, Dhanashree; Shirke, D. T.; Jadhav, Prashant
Abstract : The aim of the study was to determine influence of intellectually disability (ID) on oral hygiene status (OHS), periodontal status (PS), and periodontal treatment needs (PTNs) and investigate the association of these clinical parameters with various sociodemographic and clinical variables among multicentric institutionalized ID subjects aged 5–55 years in Kolhapur district, Maharashtra, India. This descriptive cross-sectional study was conducted by both questionnaire and clinical examination. OHS, PS, and PTNs of these subjects were assessed by recording Simplified Oral Hygiene Index (OHI-S) and Community Periodontal Index of Treatment Needs, respectively. Analysis of variance and multiple logistic and stepwise linear regression analysis were used for statistical analysis. Of the 576 subjects examined, the mean age of the subjects was 17.50 ± 7.4 years. Subjects with profound level of ID had the highest mean OHI-S, PS, and PTNs scores of 4.47 ± 1.04, 2.84 ± 0.78, and 2.25 ± 0.44, respectively, as compared with other ID groups (P < 0.0001 ). The present study signified that ID subjects had poor OHS and PS with the highest PTNs and were influenced by age (P < 0.0001 ), degree of ID (P < 0.0001 ), SES, location, institution type, and parent's level education. The present study underlines a considerable need for prevention and treatment of periodontal disease among ID subjects in India.